Biodiversity, Distribution and Host Range of the Genus Ephedrus Haliday (Hymenoptera: Aphidiidae) in Manipur, N.E. India - and T.K. Singh, P.M. Singh*, P. Devjani, Kh. Devikarani (Journal of Experimental Sciences, 2011)
The aphidiid wasps are small ichneumonoid hymenopterous insects which are strictly specific solitary endophagous parasitoids of the aphids. They are amongst the most important group of parasitic insects that can be utilized as bio-control agent of aphids. So far 60 genera of aphidiid parasitoids have been described from all over the world. Out of these the genus Ephedrus Haliday is a common one. An extensive study of this genus along with their aphid hosts in different localities of Manipur during 2007- 2008 revealed the occurrence of 13 species belonging to the genus viz. Ephedrus brevis, E. cerasicola, E. dioscorae, E. lacertosus, E. minor, E. nacheri, E. niger, E. orientalis, E. persicae, E. plagiator, E. srinagarensis, Ephedrus sp.a and Ephedrus sp.b. The parasitoids revealed variations in terms of their altitudinal distribution (from 785m.to 1920 m. MSL).Ã‚Â Most of the parasitoid species exhibited host specificity however E. plagiator showed extreme polyphagy parasitizing 4 aphid host species infesting different host plants.